2023
DOI: 10.1002/adfm.202302877
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Radioactive Gas with Scintillating MOFs

Abstract: Homogenous radioactive gas contamination constitutes the hardest challenge for radioprotection due to its elusive nature. Most common radioactive gas are 85 Kr, 222 Rn, and tritiated ( 3 H) vapors. Each of them has different challenges, often leading to specialized single-gas detectors. The state-of-the-art detection either produces chemical-radiological waste, is hard to implement online, or requires large volume. A new paradigm is presented for radioactive gas detection that can perform online detection on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Exploiting the cavity structure of MOFs, novel possibilities like self‐detection of radioactive gases (e.g., 222 Rn, 85 Kr, and 3 H) can be conceived. [ 20,27 ] Future research endeavors are poised to concentrate on refining detection limits while aligning with environmental policies and regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting the cavity structure of MOFs, novel possibilities like self‐detection of radioactive gases (e.g., 222 Rn, 85 Kr, and 3 H) can be conceived. [ 20,27 ] Future research endeavors are poised to concentrate on refining detection limits while aligning with environmental policies and regulations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] The design of M 6 ( µ 3 ‐O) 4 ( µ 3 ‐OH) 4 (carboxylate) 12 (M═Hf or Zr) MOFs by Lin and coworkers in 2014 marked a turning point in the landscape of modern research of efficiently converting X‐ray to visible light. [ 10 ] Since then, a variety of radiation‐responsive MOFs have been created with outstanding properties such as autoluminescence, [ 11 ] multicolor tunability, [ 12 ] and fast scintillation, [ 13 ] which have enabled innovative applications in the fields of biomedical therapy, [ 16,26 ] advanced sensing, [ 20,27 ] and non‐destructive imaging. [ 28 ] Notably, a recent study on transparent sintered MOFs revealed that excellent scintillation properties can be well preserved after high‐temperature and high‐pressure treatment, [ 14 ] laying the foundation for high‐quality X‐ray imaging based on bulk MOFs scintillators.…”
Section: Introductionmentioning
confidence: 99%
“…PC 1-8 had obvious responses to five VOCs, which was due to two reasons: first, the characteristic properties of MOFs, that is, the vapor can usually be concentrated to a higher level. [53] Meantime, there are a large number of voids in the PCs stacked by all nanoparticles (Figures S14 and S15, Supporting Information). The interconnected pores are conducive to the diffusion of VOCs in the PC, and occur capillary condensation in the porous structure, which further aggravates the RI change of the MOF layers.…”
Section: Sensing Performance Of Common Solvent Vaporsmentioning
confidence: 99%
“…Broad chemical and thermal stability is one of the highly sought-after traits in the field of metal–organic frameworks (MOFs ), which shapes the landscape of possible applications with a main focus on specific MOF classes, including those based on zirconium. Indeed, Zr-MOFs (e.g., possessing fcu- , and ftw-type , topologies) exhibit excellent thermostability up to 500 °C, possess chemical stability across a wide pH range from 2 to 12, and demonstrate exceptional resilience even under 423 Gy/min γ radiation . At the same time, the recent and rapidly growing interest in the development of fuel cycle reactors, radiological daughters for nuclear medicine, and efficient nuclear stockpile recycling serves as the driving force for translating the wealth of fundamental knowledge acquired for Zr-MOFs to thorium-based analogs. Since the onset of research focusing on Th-based materials, Zr-frameworks have been considered to be the closest analogs due to the shared metal oxidation state (+4), high Lewis acidity, formation of strong coordination bonds to carboxylate-based organic linkers, and oxophilicity comparable to thorium. However, in contrast to a plethora of publications (>3600) focusing on Zr-MOFs, only around 100 exist for their Th-based counterparts (Figure ).…”
Section: Introductionmentioning
confidence: 99%